The vegetation of Antarctica through geological time - Cantrill, David J., 1962- (Cambridge University Press, 2012)
"The fossil history of plant life in Antarctica is central to our understanding of the evolution of vegetation through geological time and also plays a key role in reconstructing past configurations of the continents and associated climatic conditions. This book provides the only detailed overview of the development of Antarctic vegetation from the Devonian period to the present day, presenting Earth scientists with valuable insights into the break up of the ancient supercontinent of Gondwana. Details of specific floras and ecosystems are provided within the context of changing geological, geographical and environmental conditions, alongside comparisons with contemporaneous and modern ecosystems. The authors demonstrate how palaeobotany contributes to our understanding of the palaeoenvironmental changes in the southern hemisphere during this period of Earth history. The book is a complete and up-to-date reference for researchers and students in Antarctic palaeobotany and terrestrial palaeoecology"--